Passos para Cristo: a construção do conceito de "santificação" na obra de Ellen White legada à Igreja Adventista do Sétimo Dia - Darius, Fábio Augusto (2010)
This research approaches the background of the concept of sanctification from the historical development of the Seventh-Day Adventist Church, mainly under the view of its co-founder's writings, Ellen Gould Harmon White, between 1844 and 1915. The first of the four chapters deals with the origins of the movement that preceded Adventism by farmer William Miller. From his interpretation of the bible, he concluded that the end of the world with the culminating literal return of Christ would be imminent and the preparation for the encounter with the Lord was the main subject of his work, establishing the dearest hope of the Millerite believers and, later, of the seventh-day adventists. The second chapter approaches in a summed way Ellen White's biography and her effective participation in the doctrinal construction of the studied denomination, while the third approaches specifically the origins of the Seventh-Day Adventist Church and its effort to establish itself as a denomination in the purposes of historical protestantism. Finally, the fourth chapter examines the preceding ones from Ellen White's concepts of sanctification, established during the long background process of the Adventist identity.